Pengaruh Jumlah Uang Saku Pelajar terhadap Pilihan Permainan (Tradisional dan Modern) di Mi Miftahul Huda Dusun Kaligoro Desa Sukomaju - Wulan Ndari, Dewi; Soetopo, Dhalia (Universitas Sarjanawiyata Tamansiswa, 2024)
Toys are objects or tools designed for the purpose of entertainment, learning, or recreational activities. Technological advances and the wide flow of information via the internet have shaped the lifestyle of Generation Z. They are used to communicating using gadgets, getting information from various sources via the internet, playing games, and even shopping using smartphones, a device that is always in their hands. Pocket money plays a key role in shaping the financial independence of children and teenagers. Pocket money can impact access to technology, including devices and internet connections. This article will examine the influence of the amount of pocket money on students' game choices, with a focus on traditional and modern games. The type of research carried out is quantitative research, where the researcher uses a causality design to test the relationship between variable X as the independent variable, namely the amount of pocket money, and variable Y as the dependent variable, namely the choice of game. The amount of pocket money has a significance value of 0.017. This value is smaller than 0.05 (0.017 < 0.05). The hypothesis stating that there is a relationship between the amount of pocket money and the choice of game is accepted. This means that pocket money influences the choice of games, both traditional and modern.